Pemberdayaan Petani Melalui Pembuatan Alat Penebar Pupuk di Desa Bintan Buyu: Pengabdian - Muhammad Riza Mahendra; Anggraheni Juwita Fransisco; Fedra Sitanggang; Desy Natalia; Fitra Restu Yunisa; Fadiah Syafila; Zulka Ladini Hanifah; Hammam Anwar Muhammad; Tri Febriansyah Putra; Nur Fadli Hasniadi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Real Work Lecture Program (KKN) Group 20 of Raja Ali Haji Maritime University (UMRAH) in Bintan Buyu Village aims to solve the issue of manual fertilization in the agricultural sector by making a simple fertilizer spreader. The approach applied includes making tools from readily available materials, demonstrations of their use, training for farmers, and testing the effectiveness of tools in the field. Key findings show that the tool can evenly distribute fertilizer at a dose of about 5 grams per pressure, speed up fertilization time by up to 50%, reduce labor and costs, and increase yields. The active participation of farmers in the development and use of these tools supports the sustainability of the program, which provides positive benefits both socially and economically. In conclusion, this simple fertilizer spreader innovation has proven to be the right technological solution to increase agricultural efficiency and productivity in Bintan Buyu Village.